Barriers to Screening for Anal Dysplasia and Strategies to Overcome Them - Arsoniadis, Elliot G.; Bennis, Sarah; Wheldon, Christopher W. (Clinics in Colon and Rectal Surgery, 2025)
Barriers to anal dyplasia screening are numerous and multifactorial. It is a rare disease, comprising only 2.5% of all gastrointestinal malignancies. Of the populations at high risk, men who have sex with other men (MSM), especially those living with HIV, represent the most studied high-risk population. Although knowledge of human papillomavirus (HPV) is relatively high in this population, its link to anal cancer and self-perception of risk of anal cancer in this population remains low. There are little, if any, data on provider knowledge or awareness of anal dysplasia or the high-risk populations that would benefit from screening. Given the recent advent of comprehensive anal cancer screening guidelines by the International Anal Neoplasia Society, this gap in knowledge is not suprising. Even among providers aware of these guidelines, other barriers exist, including possible discomfort discussing anal health, sexual practices, or discomfort in the performance of the screening test. Providers may also face challenges interpreting results of screening tests or finding specialists in high-resolution anoscopy for referral in the instance of a positive screening test. Finally, MSM and persons living with HIV have historically experienced stigmatization within the health care system. These historical underpinnings further complicate efforts to implement screening programs in these populations.
Keywords: cancer screening; implementation science; anal dysplasia; LGBT health; sexual and gender minority cancer